Nonlinear and symptom specific associations between chronotype and depression - Lennart Seizer; Estefanía Martínez-Albert; Johanna Löchner (Scientific Reports)
Abstract The chronotype of individuals has been found to be predictive of depression risk and associated with the severity of depression. However, since depression is a phenotypically heterogeneous disease, it seems improbable that chronotype plays a role in every instance of depression. This study investigates the association between the two, while considering possible symptom-specificity and non-linearity of the relationship, utilizing a large sample from the National Health and Nutrition Examination Survey (N = 5217; 54% female; Age: M = 52.65, SD = 18.76). Depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9), and chronotype was determined by calculating sleep midpoints. Further, we also explored the potential mediating role of systemic inflammation, measured by C-reactive protein (CRP) levels, in the chronotype-depression link. The findings substantiate previous research indicating late chronotypes to be associated with higher PHQ-9 sum scores, with a minimum in PHQ-9 at a sleep midpoint of 02:49. The study further differentiates between individual depression symptoms, uncovering varying patterns of association with chronotype. No significant effect of chronotype on levels of CRP was found, suggesting that the link between chronotype and depression symptoms may not be directly mediated and appears to be stable and independent from systemic inflammation. The study highlights the non-linear and symptom-specific nature of the chronotype-depression connection and suggests the need for further, longitudinal studies to elucidate causal mechanisms and potential mediators.